Аpplied a Conditions of Smoothness of Causal Relationships in the Problem of Constructing of Mathematical Models - Silvestrov, Anton; Spinul, Ludmila; Serdiuk, A. A. (My University, 2020)
The publication, based on the fundamental property of all real processes, namely the smoothness of nonlinear causal relationships between the variables of the state of the object of identification and the variables themselves, presents a few of new identification methods that are simpler and more accurate than traditional. These methods are illustrated by examples of estimating the aerodynamic coefficients and balancing characteristics of aircraft, building a single mathematical model of the magnetization curve.
Keywords: identification; ідентифікація; smoothness; плавність; hammerstein model; модель Гаммерштейна; natural experiment; природний експеримент; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки